Programme costs of longer and shorter tuberculosis drug regimens and drug import: a modelling study for Karakalpakstan, Uzbekistan. Issue 1 (21st March 2022) - Kohler, Stefan; Sitali, Norman; Achar, Jay; Paul, Nicolas
Background: The introduction of new and often shorter tuberculosis (TB) drug regimens affects the cost of TB programmes. Methods: We modelled drug purchase and import costs for 20-month, 9-month and 4- to 6-month TB drug regimens based on 2016–2020 treatment numbers from a TB programme in Karakalpakstan, Uzbekistan, and 2021 Global Drug Facility prices. Results: On average, 2225±374 (±sd ) people per year started TB treatment, 30±2.1% of whom were diagnosed with drug-resistant forms of TB. Transitioning from a 6-month to a 4-month drug-susceptible (DS)-TB drug regimen increased the TB programme's annual DS-TB drug cost from USD 65±10 K to USD 357±56 K (p<0.001) and its drug import cost from USD 6.4±1.0 K to USD 9.3±1.4 K (p=0.008). Transitioning from a 20-month all-oral multidrug-resistant (MDR)-TB drug regimen to a 9-month MDR-TB drug regimen with an injectable antibiotic decreased the TB programme's annual MDR-TB drug cost from USD 1336±265 K to USD 266±53 K (p<0.001) and had no significant effect on the drug import cost (USD 28±5.5 K versus USD 27±5.4 K; p=0.88). Purchasing (USD 577±114 K) and importing (USD 3.0±0.59 K) the 6-month all-oral MDR-TB drug regimen cost more than procuring the 9-month MDR-TB drug regimen but less than the 20-month all-oral MDR-TB drug regimen (both p<0.01). Conclusion: Introducing new and shorter TB drug regimens could increase the cost of TB programmes with low drug resistance rates and decrease the cost of TB programmes with high drug resistance rates. Introduction of new TB drug regimens can increase or decrease programme expenses for drug purchase and import. Modelling programme costs of different drug regimens can inform financial planning and help prepare TB programmes for changes in treatment. https://bit.ly/3r8coRj